Fly ash effect on mechanical properties of concretes made with high absorbent crushed limeston aggregates - Mendoza Rangel, José Manuel (Asociacin Latinoamericana de Control de Calidad, Patologa y Recuperacin de la Construccin, 2016)
Concrete made with high-absorbent crushed limestone aggregates from Yucatán, México are well known as a low quality concrete. The aim of this investigation is to enhance the mechanical properties of concrete with high absorbent crushed limestone aggregates and fly ash. The measured properties were: compressive strength and elastic modulus. The water/cement ratios were 0.5 and 0.7, fly ash was incorporated as partial substitution of cement with 20% and 40% and as a mineral additive in 10% and 20%. Results show that fly ash can be used in this kind of concretes as mineral additive due to compressive strength was similar to those reference samples. Finally, an equation for predicting mechanical properties is reported.